2022
DOI: 10.36227/techrxiv.19180643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accurate High Frequency Modelling of the Input Admittance of PWM Grid-Connected VSCs

Abstract: This paper addresses high frequency admittance modelling of current-controlled voltage source converters (VSCs). Recent studies have shown that harmonic instability may also occur at frequencies above the Nyquist frequency. To form an accurate multiple-frequency model in this frequency range, sidebands that originate from modulation and sampling must be examined. In this paper, an accurate small-signal model is developed taking into account an adequate digital pulse-width modulator (DPWM) representation, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…where m is the modulating waveform, equal to v i,r after one step delay, and d is the continuous-time duty-cycle of x, used in averaged modeling [5]. From (2), it is clear that digitallycontrolled VSCs exhibit operating point dependency, which is often overlooked when using delay or ZOH models for the DPWM, due to its limited impact at low and medium frequencies [45]. However, in [45], it is shown that this nonlinearity may yield significant impacts in the high frequency range.…”
Section: A S-domain Representationmentioning
confidence: 99%
See 3 more Smart Citations
“…where m is the modulating waveform, equal to v i,r after one step delay, and d is the continuous-time duty-cycle of x, used in averaged modeling [5]. From (2), it is clear that digitallycontrolled VSCs exhibit operating point dependency, which is often overlooked when using delay or ZOH models for the DPWM, due to its limited impact at low and medium frequencies [45]. However, in [45], it is shown that this nonlinearity may yield significant impacts in the high frequency range.…”
Section: A S-domain Representationmentioning
confidence: 99%
“…From (2), it is clear that digitallycontrolled VSCs exhibit operating point dependency, which is often overlooked when using delay or ZOH models for the DPWM, due to its limited impact at low and medium frequencies [45]. However, in [45], it is shown that this nonlinearity may yield significant impacts in the high frequency range. For D = 0.5, DPWM model reduces to a pure time delay e −s Ts 2 .…”
Section: A S-domain Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that these measurements were conducted, and the results were found to be somewhere in between dc results for all operating points in the sinusoidal ac range. More considerations on this can be found in [42], [45].…”
Section: Experimental Setup and Admittance Measurements For Ds-pwm Wi...mentioning
confidence: 99%